Comparing the sensitivity of two cogeneric ascidian species to two plastic additives: Bisphenol A and the flame retardant tris(chloro-propyl)phosphate. Issue 1 (31st December 2022) - Mercurio, S.; Messinetti, S.; Barzaghi, B.; Pennati, R.
Abstract: Although sensitivity to pollutants is well known to be species specific, closely related species are often assumed to respond similarly to them. We tested this assumption, comparing the sensitivity of Ciona intestinalis and Ciona robusta to two common marine pollutants: Bisphenol A (BPA) and tris(1-chloro-2-propyl)phosphate (TCPP). In particular, we focused on ascidian embryonic development and determined whether C. intestinalis and C. robusta displayed different responses. Our results demonstrate that closely related species can display either similar or very different sensitivity based on the tested contaminant. Ciona intestinalis and C. robusta had similar sensitivity to BPA, as their median effective concentration (EC50 ) and median lethal concentration (LC50 ) values were comparable. In contrast, TCPP showed very different teratogenic potential in the two analyzed species. Ciona robusta proved more vulnerable to this flame retardant as its teratogenic index was more than twice that calculated for C. intestinalis . Chemical modes of action as well as genetic differences could determine the diverse responses to environmental stressors. These results underline the presence of species-specific differences in embryonic sensitivity to contaminants and point out the importance of evaluating chemicals' teratogenic profile in several species.